How Does Mentoring Affect the Creative Performance of Mentors: The Role of Personal Learning and Career Stage - Xu, Shuang; Liu, Pingqing; Yang, Zheng; Cui, Zunkang; Yang, Fang (Frontiers in Psychology, 2021)
Mentoring has become a vital strategy for improving employee performance and organizational development. A few previous literature studies made a detailed study on the benefits of mentees. The creative performance of mentors that improves from mentoring, however, only draws little attention. This article extends this line of inquiry by shedding light on whether, how, and when mentoring affects the creative performance of mentors, which is a crucial topic in research and practice. Based on the conservation of the resources theory (COR) and relational cultural theory (RCT), this article investigates the influence mechanism and boundary conditions of mentoring on the creative performance of mentors by conducting a multisource empirical study in China. The result shows that there is a positive impact of mentoring on the creative performance of mentors. We also reveal that the relationship is mediated by personal learning, especially the relational job learning dimension. Furthermore, this article finds that the career stage of mentors moderates the relationship between mentoring and personal learning, namely, the relationship is stronger among mentors at the later career stage. The empirical findings show implications for an understanding of how the creative behavior of mentors benefits mentoring and can be beneficial for developing the targeted measures to promote competitive advantages for organizations.